Simulations of a Single-Phase Flow in a Compound Parabolic Concentrator Reactor - Tzayam Pérez; José L. Nava (International Journal of Photoenergy)
This paper deals with the analysis and interpretation of flow visualization and residence time distribution (RTD) in a compound parabolic concentrator (CPC) reactor using computational fluid dynamics (CFD). CFD was calculated under turbulent flow conditions solving the Reynolds averaged Navier–Stokes (RANS) equation expressed in terms of turbulent viscosity and the standard k−ε turbulent model in 3D. A 3D diffusion-convection model was implemented in the CPC reactor to determine the RTD. The fluid flow visualization and RTD were validated with experimental results. The CFD showed that the magnitude of the velocity field remains almost uniform in most of the bulk reactor, although near and inside the 90° connectors and the union segments, the velocity presented low- and high-speed zones. Comparisons of theoretical and experimental RTD curves showed that the k−ε model is appropriate to simulate the nonideal flow inside the CPC reactor under turbulent flow conditions.